Efficiency Assessment of Cruciform Steel Columns: Balancing Axial Capacity and Weight - Keintjem, Militia; Suwondo, Riza; Suangga, Made (Engineering, Technology & Applied Science Research, 2025)
Cruciform steel columns, also known as king and queen cross sections, have gained attention in structural engineering for their ability to overcome the limitations of traditional I-sections and H-sections. These limitations include reduced stability due to slenderness effects and excessive material usage in tall columns. Designed to enhance axial load capacity while minimizing weight, cruciform sections offer a more efficient, cost-effective, and sustainable alternative for modern construction. This study assesses the efficiency of cruciform steel columns by comparing their design axial capacities to their unit weights. Using AISC 360-16 provisions, single supported columns with heights of 2 m, 3 m, 4 m, and 5 m were analyzed. The results show that all sections perform similarly for short columns (2 m), with efficiency differences of less than 8% due to the minimal impact of slenderness. However, at 3 m, the I-section is 20% less efficient than the H-section and 30% less efficient than cruciform sections. For taller columns (4 m and 5 m), cruciform sections outperform conventional sections, with the king cross-section proving to be 30% more efficient than the H-section and superior to the queen cross-section. These findings highlight the structural and material advantages of cruciform sections, particularly in applications requiring tall columns with significant slenderness effects. By reducing material usage while maintaining high load-bearing capacity, cruciform sections enhance sustainability by lowering both carbon and construction costs. This study provides valuable insights for optimizing steel column designs to achieve more sustainable and cost-effective construction.